The effect of acute creatine supplementation on fatigue and anaerobic performance - Ates, O.; Keskin, B.; Bayraktar, B. (Central European Journal of Sport Sciences and Medicine, 2017)
The aim of this study is to investigate the effect of acute creatine monohydrate supplementation on fatigue and anaerobic performance. Thirty young soccer players participated in this study. Participants continued their training without taking any food supplements for 5 days, taking 0.3 g of milk dust per kg for 5 days and using 0.3 g creatine monohydrate per kg for 5 days. A total of 6 × 35 m sprint times were used in the fatigue index with a 10-second rest period between them. Single repeated sprint times of 35 m were examined as well. Statistically significant differences (p < 0.05) were found both fatigue index and single repeated 35 m sprint time after creatine supplementation. However there was not a statistically significant difference (p > 0.05) in Rast Test results. In soccer, it is known that there is a strong positive correlation between game performance and the number of repeated sprint numbers in a game. In conclusion, there was a statistically significant effect of 0.3 g of acute creatine loading per kg over 5 days on the single repeated sprints and fatigue index values. The creatine monohydrate can be used as an ergogenic aid for recovery periods between high-intensity exercises to affect performance.